2021
DOI: 10.1111/liv.15033
|View full text |Cite
|
Sign up to set email alerts
|

Treatment induced clearance of hepatitis E viruses by interferon‐lambda in liver‐humanized mice

Abstract: Background: Hepatitis E viruses (HEV) are an underestimated global cause of enterically transmitted viral hepatitis, which may persist in immunocompromised hosts, posing a risk for progressive liver fibrosis with limited treatment options. We previously established liver-humanized mice as a model for chronic HEV infections, which can be cleared by a 2-week pegylated (peg)-Interferon(IFN)α treatment course.However, severe side effects may hamper the use of IFNα in immunocompromised transplant recipient patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…1b-c ). The level of IFN- λ 1 mRNA, which has known anti-viral role against HEV in mice (Sari et al, 2021) , increased upon viral replication in both cell types ( Fig. 2a-b ; left panels).…”
Section: Resultsmentioning
confidence: 94%
“…1b-c ). The level of IFN- λ 1 mRNA, which has known anti-viral role against HEV in mice (Sari et al, 2021) , increased upon viral replication in both cell types ( Fig. 2a-b ; left panels).…”
Section: Resultsmentioning
confidence: 94%
“…Various strategies [147][148][149][150][151][152][153][154] including screening of drug libraries, 155 exploration of preclinical 104 or natural 156,157 compounds as well as in silico docking 158 have been dedicated to the quest to find novel HEV inhibitors (Table 2). When transferred into T cells obtained from patients with chronic HEV, engineered T-cell receptors have been shown to recognise virus-specific epitopes and mediate killing of the target cells in cell culture, 159 indicating that T cell-based immunotherapy could be used to treat chronic HEV infection.…”
Section: Future Developmentmentioning
confidence: 99%
“…Only used for a few cases of chronic HEV; risk of causing transplant rejection Sofosbuvir 98,138,139,142 Viral RdRp inhibitor Cell lines; Stem cell-derived HLCs Rabbits Chronic HEV patients A phase II trial demonstrated failure to clear HEV in patients with chronic infection Interferon-lambda 151 Activating innate antiviral response…”
Section: Chronic Hev Patientsmentioning
confidence: 99%